DISTANCE LEARNING FOR DEVELOPING KNOWLEDGE AND SKILLS IN ENGLISH LANGUAGE TEACHING - Natalia A. Kameneva; Ludmila V. Zenina (Статистика и экономика, 2016)
The importance of using distance learning for developing knowledge, skills and competences in English Language teaching in contemporary educational process is justified in the article. In this connection the great attention is focused on radical changes in English Language teaching methodology. With the advent of online education the relationships between the lecturers or the tutors and the students alter and become more open and cooperating, because the students get more involved, interested and motivated in learning foreign languages. Apart from this, the main components of distance education are briefly considered.